Axon Guidance Mechanisms for Establishment of Callosal Connections. (24th February 2013) - Nishikimi, Mitsuaki; Oishi, Koji; Nakajima, Kazunori
Abstract : Numerous studies have investigated the formation of interhemispheric connections which are involved in high-ordered functions of the cerebral cortex in eutherian animals, including humans. The development of callosal axons, which transfer and integrate information between the right/left hemispheres and represent the most prominent commissural system, must be strictly regulated. From the beginning of their growth, until reaching their targets in the contralateral cortex, the callosal axons are guided mainly by two environmental cues: (1) the midline structures and (2) neighboring? axons. Recent studies have shown the importance of axona guidance by such cues and the underlying molecular mechanisms. In this paper, we review these guidance mechanisms during the development of the callosal neurons. Midline populations express and secrete guidance molecules, and "pioneer" axons as well as interactions between the medial and lateral axons are also involved in the axon pathfinding of the callosal neurons. Finally, we describe callosal dysgenesis in humans and mice, that results from a disruption of these navigational mechanisms.